"You Know, the South is a Breeding Ground for Gluttony": A Qualitative Evaluation of Dissonance between Christian Beliefs and Eating Habits - Karli S Yarber; Jefferson D Miller; Jill Rucker; Lora Walsh (Journal of Applied Communications, 2023)
This research is intended to initiate understanding of how obesity in the South persists even though the majority of inhabitants subscribe to a faith that discourages unhealthy lifestyles. Grounded in the Cognitive Dissonance Theory, this study examined Protestant evangelical Christians in the South (N = 11), who participated in semi-structured interviews. The first emergent theme was that, to these Southerners, the purpose of food is for sustenance and survival, as well as for bringing people together. Most participants reported having an average level of knowledge of nutrition and health. Furthermore, participants generally agreed that marketing or educational efforts had little effect on their understanding of nutrition. Another theme emerged when participants provided Biblical references to food or health. “The Body is a Temple” and “gluttony” were the most common Biblical concepts. All participants referred to taste or desirability as the driver of their food selections. Furthermore, most participants claimed habitual gluttony as a personal experience in their lives. This study concluded that subjects employed two modes of “trivializing” as a way of resolving dissonance. Some participants justified their eating habits based on Southern culture, while others explained that their church culture supported unhealthy eating as a means of gathering in fellowship.
Keywords: food marketing; religion; cognitive dissonance; communications